Jost Solution of the Matrix Difference Equations - Yardimci, Seyhmus (Sarajevo Journal of Mathematics, 2024)
In this paper, we investigate the Jost solution and the analytical properties of the Jost solution of the non-selfadjoint matrix difference equation of second order. 2000 Mathematics Subject Classification. 39A70, 47A10, 47B39